Pediatric microdose and microtracer studies using 14C in Europe. Issue 3 (17th July 2015) - Turner, MA; Mooij, MG; Vaes, WHJ; Windhorst, AD; Hendrikse, NH; Knibbe, CAJ; Kõrgvee, LT; Maruszak, W; Grynkiewicz, G; Garner, RC; Tibboel, D; Park, BK; et al.
<x xml:space="preserve">Abstract</x> Important information gaps remain on the efficacy and safety of drugs in children. Pediatric drug development encounters several ethical, practical, and scientific challenges. One barrier to the evaluation of medicines for children is a lack of innovative methodologies that have been adapted to the needs of children. This article presents our successful experience of pediatric microdose and microtracer studies using 14C‐labeled probes in Europe to illustrate the strengths and limitations of these approaches.